Multifunctional gold-nanoparticles: A nanovectorization tool for the targeted delivery of novel chemotherapeutic agentes - Fernandes, Alexandra (2017)
Due to their small size and unique properties, multifunctional nanoparticles arise as versatile delivery systems easily grafted with a vast array of functional moieties, such as anticancer cytotoxic chemotherapeutics and targeting agents. Here, we formulated a multifunctional gold-nanoparticle (AuNP) system composed of a monoclonal antibody against epidermal growth factor receptor (EGFR) (anti-EGFR D-11) for active targeting and a Co(II) coordination compound [CoCl(H2O)(phendione)2][BF4] (phendione = 1,10-phenanthroline-5,6-dione) (TS265) with proven antiproliferative activity towards cancer cells (designated as TargetNanoTS265). The efficacy of this nanoformulation, and the non-targeted counterpart (NanoTS265), were evaluated in vitro using cancer cell models and in vivo using mice xenografts. Compared to the free compound, both nanoformulations (TargetNanoTS265 and NanoTS265) efficiently delivered the cytotoxic cargo in a controlled selective manner due to the active targeting, boosting tumor cytotoxicity. Treatment of HCT116-derived xenografts tumors with TargetNanoTS265 led to 93% tumor reduction. This simple conceptual nanoformulation demonstrates the potential of nanovectorization of chemotherapeutics via simple assembly onto AuNPs of BSA/HAS-drug conjugates that may easily be expanded to suit other cargo of novel compounds that require optimized controlled delivery to cancer target.